Racial/ethnic differences in the clinical presentation and survival of breast cancer by subtype - Nhim, Vutha; Bencomo-Alvarez, Alfonso E.; Alvarado, Luis; Kilcoyne, Michelle; Gonzalez-Henry, Mayra A.; Olivas, Idaly M.; Keivan, Mehrshad; Gaur, Sumit; Mulla, Zuber D.; Dwivedi, Alok K.; Gadad, Shrikanth S.; Eiring, Anna M. (Frontiers in Oncology, 2024)
Background: Breast cancer (BC) affects racial and ethnic groups differently, leading to disparities in clinical presentation and outcomes. It is unclear how Hispanic ethnicity affects BC outcomes based on geographic location and proximity to the United States (U.S.)/Mexico border. We hypothesized that the impact of race/ethnicity on BC outcomes depends on geographic location and country of origin within each BC subtype. Methods: We analyzed BC data from the Texas Cancer Registry by race/ethnicity/birthplace according to BC subtype (luminal A/luminal B/human epidermal growth factor receptor 2[HER2]/triple-negative breast cancer [TNBC]). Other covariates included age, geographic location (U.S., Mexico), residency (border, non-border), treatments, and comorbidities. Crude and adjusted effects of race/ethnicity and birthplace on overall survival (OS) were analyzed using Cox regression methods.Results: Our analysis of 76,310 patient records with specific BC subtypes revealed that Hispanic and non-Hispanic Black (NHB) patients were diagnosed at a younger age compared with non-Hispanic White (NHW) patients for all BC subtypes. For the 19,748 BC patients with complete data on race/ethnicity/birthplace/residency, Hispanic patients had a higher mortality risk in the Luminal A subtype, regardless of birthplace, whereas U.S.-born Hispanics had a higher risk of death in the TNBC subtype. In contrast, NHB patients had a higher mortality risk in the Luminal A and HER2 subtypes. Residence along the U.S./Mexico border had little impact on OS, with better outcomes in Luminal A patients and worse outcomes in Luminal B patients aged 60-74 years.Conclusions: Race/ethnicity, geographic birth location, and residency were significant predictors of survival in BC. Migration, acculturation, and reduced healthcare access may contribute to outcome differences.